2001
DOI: 10.1097/00006324-200106000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Mouse Outer Retina

Abstract: The amplitude of the mouse ERG declines with age. This change does not appear to reflect a change in the structural integrity of the photoreceptor cells. In functional studies of murine models of late-onset retinal disorders, it will be important to take these changes into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
52
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 29 publications
25
52
1
Order By: Relevance
“…Effects on Control APB mice were much smaller. In previous studies by other investigators, the amplitudes of dark-adapted a-waves and b-wave were found to be reduced as mice aged for both C57BL/6 mice (pigmented mice) and Balb/c mice (albino mice) (Gresh et al, 2003;Li et al, 2001). Between four and 17 months of age, there was a substantial loss of rod photoreceptors (more in the albino mice), which contributed to the reduced ERG amplitudes.…”
Section: Effects Of Aging On the Light-adapted Erg Of Mice Lacking B-mentioning
confidence: 77%
See 3 more Smart Citations
“…Effects on Control APB mice were much smaller. In previous studies by other investigators, the amplitudes of dark-adapted a-waves and b-wave were found to be reduced as mice aged for both C57BL/6 mice (pigmented mice) and Balb/c mice (albino mice) (Gresh et al, 2003;Li et al, 2001). Between four and 17 months of age, there was a substantial loss of rod photoreceptors (more in the albino mice), which contributed to the reduced ERG amplitudes.…”
Section: Effects Of Aging On the Light-adapted Erg Of Mice Lacking B-mentioning
confidence: 77%
“…Between four and 17 months of age, there was a substantial loss of rod photoreceptors (more in the albino mice), which contributed to the reduced ERG amplitudes. But aging effects have been less obvious for cones, whose counts (middle wavelength) were reduced in aged Balb/c mice, but not in C57BL/6 mice (Gresh et al, 2003;Jacobs and Williams, 2007;Li et al, 2001). Cone-driven flash ERGs were found to be reduced in mice that are a year old, and light-adapted flicker ERG amplitudes were affected, but only mildly in the pigmented mice (Jacobs et al, 2007;Li et al, 2001).…”
Section: Effects Of Aging On the Light-adapted Erg Of Mice Lacking B-mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we examined whether the dark-adapted ERG abnormalities of nob2 mice also were stable and recorded ERGs at 3, 7, and 15 months of age. To compensate for the reduction in overall amplitude that occurs in older WT mice (Li et al, 2001), values are expressed as a percentage of the mean for agematched WT mice recorded under the same conditions. At each age tested, the maximum awave amplitude, represented by the Rm P3 values, from nob2 mice were not different from those of WT animals (Fig.…”
Section: Ergs Are Abnormal In Nob2 Micementioning
confidence: 99%